klaudia771
12

# rozwiąż równania -(x+3)+(2x-1)=(1+4x)+(3+x) -(x+3)-(2x+8)=(-3-2x)-(2x +1) (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7) (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7) (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6) -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)

(2) Odpowiedź
AniulQaaa

-(x+3)+(2x-1)=(1+4x)+(3+x) -x - 3 + 2x - 1= 1 + 4x + 3 + x - 3 + 2x - 1= 1+ 4x + 3 - 4 -1 -3 = 4x - 2x - 8 = 2x (zamiana stronami) 2x = - 8 | :2 x = - 4 -(x+3)-(2x+8)=(-3-2x)-(2x +1) - x - 3 - 2x - 8 = -3 - 2x -2x -1 - 3x - 11 = - 4 - 4x 4x - 3x = 11 - 4 x = 7 (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7) 3 - 2x - x - 4 -2x - 5 = 3x - 4 -5x - 7 3 - 5x - 5 - 4 = - 2x - 11 -5x + 2x = - 11 - 3 +9 - 3x = 5 | : (-3) x = - 1 i 2/3 (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7) 4 - x - 2x - 3 + x - 4 = - 2x + 3 -x -7 4 - 2 x - 7 = - 3x - 4 - 2x + 3x = 7 x= 7 (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6) 4x - 5 + x -7 - 2x + 8 = -3x + 4 -x +6 3x - 12 + 8 = - 4x + 10 3x + 4x = 10 +12 - 8 7x = 14 | :7 x = 2 -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x) - 4 + 2x -2x -4 = 3x-1 +2x - 5 -7 + 3x - 8 = 8x - 13 13 - 8 = 8x 8x = -5 x = - 5/8

strawberryxd

-(x+3)+(2x-1)=(1+4x)+(3+x) -x-3+2x-1=1+4x+3+x -x+2x-4x-x=1+3+1+3 -4x=8/(-4) x=(-2) -(x+3)-(2x+8)=(-3-2x)-(2x +1) -x-3-2x-8=-3-2x-2x-1 -x-2x+2x+2x=-3-1+3+8 x=7 (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7) 3-2x-x-4-2x-5=3x-4-5x-7 -2x-x-2x-3x+5x=-4-7-3+4+5 -3x=-5/ (-3) x=1 ²/₃ (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7) 4-x-2x-3+x-4=-2x+3-x-7 -x-2x+x+2x+x=-7-4+3+4 x=(-4) (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6) 4x-5+x-7-2x+8=-3x+4-x+6 4x+x-2x+3x+x=4+6+5+7-8 7x=14/7 x=2 -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x) -4+2x-2x-4=3x-1+2x-5-7+3x 2x-2x-3x-2x-3x=-1-7-5+4+4 -8x=-5/ (-8) x=⁵/₈

Dodaj swoją odpowiedź